Sosialisasi Model Pembelajaran Inkuiry Terbimbing untuk Melatih Kolaborasi Peserta Didik di SMP Negeri 2 Sleman Yogyakarta - Putri Aisyah; Masnaeni; Jum'anil Agustini; Nur Rizki Awalia; Miftahul Muflihah; Hejeriani; Majid, Ahmad Farham (KHIDMAH: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve students' collaborative skills and understanding of mathematical concepts through the application of a guided inquiry learning model on exponential material at SMP Negeri 2 Sleman, Yogyakarta. The activity was carried out over 45 days through six stages, namely initial observation, preparation of teaching tools, socialization of the learning model, explanation of the material, implementation of group learning, and presentation and reflection on the results of the activity. An observation instrument was used to assess five indicators of student collaboration skills, namely active contribution, productive work, responsibility, flexibility and compromise, and mutual respect. The results of the community service showed an increase in all aspects of collaboration skills with an average increase of 21%. The highest increase occurred in the flexibility and compromise indicator at 23%, which shows that students are increasingly able to adapt and work together with their group mates. In addition, students' conceptual understanding of exponential rules also improved through discussion activities and contextual problem solving. Thus, the application of the guided inquiry learning model was effective in fostering collaboration and deepening students' mathematical conceptual understanding in exponential learning.